Learning Quality Improvement through the Metacognitive Keywords Model (MKM) Teaching Model in Islamic Learning - Supa'at Supa'at; Khilman Rofi Azmi (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2019)
The dynamics of developmental technology and information in the Postglobalization era has a significant impact in building the scientific method of education, especially for Islamic Education. The teacher or Tutor as the main actor in delivering the learning material in the classroom is required to be able to map and guide students in understanding and implementing Islamic value. This article aims to developing PAI learning models through the Metacognitive Keyword Model (MKM). A teaching method intended for teachers / tutors so that they can guide their own thoughts in delivering the material appropriately, effectively and efficiently. The term